PERPADUAN KONSEP LOKAL SUNDA DAN MILENIAL PADA DINDING LOBBY MUSEUM GEOLOGI BANDUNG - Janice Kristin; Augustina Ika Widyani (PROSIDING SERINA, 2021)
Decorative element isa part of the interior with aesthetics value and designed to increase interior value. In addition to adding aesthetic value, it can also fulfill the functional aspects of the interior. The decorative elements that will be placed in the lobby area of the Bandung Geological Museum must be designed properly so that they can represent the image of the museum, the local Sundanese concept according to its nickname as the Bandung History Icon, and adapt to the lifestyle and desires of millennial society. Something new and unique that is placed in the first area which is reached by museum visitors, it will increase the interest and curiosity of every visitor. It can also attract the attention of other people who have not come yet. This article aims to explain how the application of local Sundanese concepts combined with millennial concepts to form a new pattern that is applied to decorative elements in the lobby area of the Bandung Geology Museum. The method consists of 2 stages, analysis - programming and synthesis - schematic design. The analysis process resulted in the formation of a new pattern that adapted the local Sundanese concept, namely TariJaipongan combined with the meaning of Bandung Geological Museum logo, as well as the application of colors adapted to the Bandung Geological Museum logo to strengthen the museum's image. This decorative element is expected to attract more people to visit one of the most famous museums in Bandung.